FLEKSIBILITAS INTERIOR DALAM MENUNJANG SIFAT TEMPORARITY PADA RUANG POSYANDU - Annisa Marwati; Nia Namirah Hanum (RUSTIC, 2022)
This study discusses the concept of flexibility in Interior Design that can be applied to posyandu spaces to support the effectiveness and efficiency of providing temporary posyandu spaces. The purpose of this study is to propose more effective and efficient interior concept idea for the posyandu space, both in terms of time and effort, without compromising the function of the space itself. The implementation of routine posyandu activities has proven to have a good impact on the health status of children under five. In this case, the provision of space for posyandu activities needs to be continuously improved to improve health services in Indonesia. The research was conducted by qualitative approach with literature studies and case studies as the main sources of reference. The results of this study indicate that the posyandu space has several spatial characteristics, such as (1) independent and temporary, (2) multifunctional, (3) serving at least 5 (five) series of activities, and (4) requiring a storage area. To support these characteristics, this study carries the idea of flexibility in interior design that is collapsible/demountable and also movable. An example of this concept is also given to provide initial reference of flexibility in interior design that can be applied for posyandu.